In-Between Space/Time: Affective Exceptionality during the ‘Refugee Crisis’ in Northern Finland - Seppälä, Tiina; Nykänen, Tapio; Koikkalainen, Saara; Mikkonen, Enni; Rainio, Minna (Nordic Journal of Migration Research, 2020)
This article analyses the ‘European refugee crisis’ in the context of Northern Finland, building on the concepts of exceptionality and affect. Conventionally, exceptionality is conceptualised from the perspective of the state that does not enable analysing exceptional situations in their broader social context. A shift in focus is required to understand how people perceive and experience exceptionality and what kinds of affects this involves. Based on participatory engagement and in-depth interviews with asylum-seekers living in reception centres in Northern Finland and local residents in their neighbourhood, our analysis demonstrates that exceptionality gains diverse meanings in different contexts. We propose affective exceptionality as a conceptual tool for analysing affects in transformational situations in which people’s sense of the ‘normal’ becomes disrupted and illustrate how placing emphasis on subjects who experience and embody exceptionality in their everyday lives enables a more nuanced understanding of exceptionality, centralising the people instead of the state.